Akhila’s Journey to Explore ‘Self’ in Anita Nair’s Ladies Coupe - Ms. Kajal Paghdal (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Anita Nair is a living postmodern Indian woman writer in English. As a woman writer, she goes deep into the inner mind of the depressed women by virtue of their feminine sensibility and psychological insight and brings to light their issues, which are the outcome of Indian women’s psyche and emotional inequalities in a male dominated society. Anita Nair’s Ladies Coupe has turned out to be a great success. Her novel provides a realistic description of continuous efforts of women for the establishment of their identity in male dominated society. It is the story of a women’s search for freedom and wish to live desired life. The novel raises the questions whether the role of an Indian woman as a representative of other women, living under oppressive patriarchal systems in relation to cultural resistance, should be restricted only to their roles as wives and mothers. In such a world, woman’s role is limited to reproduction regardless of her own desires and needs. The present study was aimed on exclusive focus on Nair’s major concern in her novel i.e., theme of agony and pain of women in the patriarchal society to explore self.